Techno-economic and financial analyses of hybrid renewable energy system microgrids in 634 Philippine off-grid islands: Policy implications on public subsidies and private investments - Castro, Michael T.; Pascasio, Jethro Daniel A.; Delina, Laurence L.; Balite, Paul Heherson M.; Ocon, Joey D. (Energy (Oxford), 2022)
In line with one of the objectives of Sustainable Development Goal 7 to close energy poverty, the techno-economic feasibility of deploying hybrid renewable energy systems (HRES) in Philippine off-grid islands has been extensively studied to address reliance on diesel generators in these areas. Several works have analyzed HRES deployment at a nationwide level in terms of levelized costs, but the financial sustainability in terms of profits and subsidies of such schemes is largely unexplored. In this work, we analyzed the potential profits and subsidy requirements of HRES in 634 Philippine off-grid islands. First, we developed a database of inhabited off-grid islands containing their load profiles and solar and wind resources. A techno-economic analysis was then performed by sizing HRES with solar photovoltaics, wind turbines, lithium-ion batteries, and diesel generators in each island to minimize net present costs. A profitability analysis was then carried out by calculating profitability metrics, such as the net present value, internal rate of return, and payback period at various tariff rates. The techno-economic analysis revealed that larger islands had a higher proportion of RE technologies, which decreased long-term costs but increased capital costs. Meanwhile, the profitability analysis showed that HRES projects in larger islands become profitable at lower electricity rates but require larger subsidies to maintain when they are unprofitable. In this regard, we argue that government subsidies should be targeted towards smaller islands, while the private sector should be enticed to invest in larger islands. This work demonstrates that quantifying subsidies and profits, and not just the costs, of HRES can yield better insights on the economics of HRES deployment. Moreover, this work highlights the importance of government subsidies and private sector participation for achieving 100% energy access in the Philippines. •Financial sustainability of electrifying off-grid islands with HRES was analyzed.•Assessed profits and subsidies of HRES in 634 Philippine off-grid islands.•Large islands (>100 kW peak) have lower levelized costs but higher capital costs.•Large islands become profitable 25% above the national breakeven electricity rate.•Subsidize smaller islands (<100 kW peak); open large islands to the private sector.